Respuesta :
Answer:
(f-g) (x) = -x² + 3x + 7
Explanation:
We are given that:
f (x) = 3x + 1
g (x) = x² - 6
We want to find (f-g) (x), we can simply obtain the result by subtracting g (x) from f (x) as follows:
(f-g) (x) = f (x) - g (x)
(f-g) (x) = 3x + 1 - (x²-6)
(f-g) (x) = 3x + 1 - x² + 6
(f-g) (x) = -x² + 3x + 7
Hope this helps :)
(f-g) (x) = -x² + 3x + 7
Explanation:
We are given that:
f (x) = 3x + 1
g (x) = x² - 6
We want to find (f-g) (x), we can simply obtain the result by subtracting g (x) from f (x) as follows:
(f-g) (x) = f (x) - g (x)
(f-g) (x) = 3x + 1 - (x²-6)
(f-g) (x) = 3x + 1 - x² + 6
(f-g) (x) = -x² + 3x + 7
Hope this helps :)
Answer:
Option (b) is correct.
[tex](f-g)(x)=-x^2+3x+7[/tex]
Step-by-step explanation:
Given : Functions [tex]f(x) = 3x +1[/tex] and[tex]g(x) = x^2-6[/tex]
We have to choose the correct option from the given options that represents (f-g)(x)
Consider the given functions
[tex]f(x) = 3x +1[/tex] and[tex]g(x) = x^2-6[/tex]
then , (f - g)(x) = f(x) - g(x)
Substitute, we have,
[tex]f(x) - g(x)=3x+1-(x^2-6)[/tex]
Applying plus - minus rule[tex]-(-a)=a[/tex], we have,
[tex]f(x)-g(x)=3x+1-x^2+6[/tex]
Simplify and write in standard form, we have,
[tex]f(x)-g(x)=-x^2+3x+7[/tex]
Thus, The[tex](f-g)(x)=-x^2+3x+7[/tex]